Residual Pulmonary Vascular Resistance Increase Under Left Ventricular Assist Device Support Predicts Long-Term Cardiac Function After Heart Transplantation - Nobutaka Kakuda; Eisuke Amiya; Eisuke Amiya; Masaru Hatano; Masaru Hatano; Masaki Tsuji; Chie Bujo; Junichi Ishida; Hiroki Yagi; Akihito Saito; Koichi Narita; Yoshitaka Isotani; et al. (Frontiers in Cardiovascular Medicine, 2022)
AimsWe compared hemodynamics and clinical events after heart transplantation (HTx) in patients stratified by the severity of residual pulmonary vascular resistance (PVR) after left ventricular assist device (LVAD) implantation for bridge to transplantation.MethodsWe retrospectively analyzed patients who had undergone HTx at the University of Tokyo Hospital. We defined the high PVR group as patients with PVR of >3 Wood Units (WU) as measured by right heart catheterization performed 1 month after LVAD implantation.ResultsWe included 85 consecutive HTx recipients, 20 of whom were classified in the high PVR group and 65 in the low PVR group. The difference in PVR between the two groups became apparent at 2 years after HTx (the high PVR group: 1.77 ± 0.41 WU, the low PVR group: 1.24 ± 0.59 WU, p = 0.0009). The differences in mean pulmonary artery pressure (mPAP), mean right arterial pressure (mRAP), and mean pulmonary capillary wedge pressure (mPCWP) tended to increase from the first year after HTx, and were all significantly higher in the high PVR group at 3 years after HTx (mPAP: 22.7 ± 9.0 mm Hg vs. 15.4 ± 4.3 mm Hg, p = 0.0009, mRAP: 7.2 ± 3.6 mm Hg vs. 4.1 ± 2.1 mm Hg, p = 0.0042, and mPCWP: 13.4 ± 4.5 mm Hg, 8.8 ± 3.3 mm Hg, p = 0.0040). In addition, pulmonary artery pulsatility index was significantly lower in the high PVR group than in the low PVR group at 3 years after HTx (2.51 ± 1.00 vs. 5.21 ± 3.23, p = 0.0033). The composite event including hospitalization for heart failure, diuretic use, and elevated intracardiac pressure (mRAP ≥ 12 mm Hg or mPCWP ≥ 18 mm Hg) between the two groups was significantly more common in the high PVR group. Residual high PVR was still an important predictor (hazard ratio 6.5, 95% confidence interval 2.0–21.6, and p = 0.0023) after multivariate Cox regression analysis.ConclusionOur study demonstrates that patients with residual high PVR under LVAD implantation showed the increase of right and left atrial pressure in the chronic phase after HTx.